Impact of Watershed Development Projects Implemented in Kerala - Babu Mathew; Venu Prasad H D; Naveena K (Journal of Extension Education, 2022)
In the present study we look into the impact of 12 diﬀerent watershed projects implemented in Kerala under the Western Ghats Development Programme on the water availability and soil conservation. The impact of the watersheds was assessed by examining the beneﬁts that each watershed oﬀered to the sample respondents, people participation in watershed programmes at diﬀerent stages, budget utilization and target achieved with the help of a semi-structured interview schedule. The data collected were analysed using cluster analysis and ANOVA. The results of the data diﬀerentiate 12 watersheds into two diﬀerent clusters with 4 watersheds in one cluster and the remaining watersheds in another. The results of the study found that there is a signiﬁcant diﬀerence in people’s participation with respect to diﬀerent stages of project execution in diﬀerent watersheds and also within each watershed. The study also pinpoints diﬀerence in achieving target and budget utilization among diﬀerent watersheds.